Analisis Lima Aspek dalam Implementasi Kebijakan Membangun Budaya Keselamatan Pasien di RSUD RA. Kartini Kabupaten Jepara - Sofiyyah, Nailil Izza; Jati, Sutop Patria; Budiyanti, Rani Tiyas (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
The efforts tobbuild patient safety culture is the first step forxachieving patient safety. RSUD RA Kartini should have implemented a good patient safety culture, because patient safety is relating to the hospital quality services. The purpose of this study is analysing the implementation of policies as effort to build patient safety culture at RSUD RA. Kartini. This study is axqualitative research with analyticalcdescriptive approach and purposive sampling technique with in-depthxinterview data collection method. Thexresearchxsubjects consisted of medical staff , Chair of the Quality and Patient Safety Committee (KMKP), Chairxof the Patient Safety Sub Committee, KMKP staff, and Head of Medical Services Division of RSUD RA. Kartini. The resultsxof the study indicate that there is no regulation or procedure of individual roles in handling incidents. Staff openness, mutual trust and awareness in reporting incidents are still low because there are some staff who do not understand the mechanism for reporting incidents. Decreasing concern among staff if an incident occurs so that are not reported. The follow-up to the patient safety incident report at the RA Kartini Hospital was not optimal because the supervision from the board office directors and KMKP, named Patient Safety Round program had not been carried out routinely. The policy implementation in building a patient safety culture at RSUD RA Kartini has not been maximal because there are several aspects that have not been implemented properly.